Three weeks to say goodbye ebook - Box, C.J (2009)
New York Times bestselling author C.J. Box delivers a novel about something that could be anyone's worst nightmare... Jack and Melissa McGuane have spent years trying to have a baby. Finally their dream has come true with the adoption of their daughter, Angelina. But nine months after bringing her home, they receive a devastating phone call... Angelina's birth father, a teenager, never signed away his parental rights—and he wants her back. Worse, his father, a powerful Denver judge, will use every trick in the book to make sure it happens. The McGuanes attempt to meet face-to-face with the father and son...but soon it becomes clear that there's something sinister about their motivations—and that love for Angelina is not one of them. A horrifying game of intimidation and double crosses begins that quickly becomes a death spiral where everyone is suspect and no one is safe. Now Jack and Melissa will stop at nothing to protect their child—even though time is running out... C.J. Box has once again written a bone-chilling thriller that will keep you guessing until the very last page.